Can multiparametric MRI rule in or rule out significant prostate cancer?. Issue 6 (November 2015) - Cornud, François; Legmann, Paul; Delongchamps, Nicolas Barry
Abstract : Purpose of review: To show how multiparametric MRI can rule in the presence of significant prostate cancer (PCa), allowing for magnetic resonance-targeted biopsies to detect aggressive tumors eligible for immediate treatment and to evaluate if mp-MRI can rule out significant tumor foci to avoid overdiagnosis and overtreatment of PCa. Recent findings: Diffusion-weighted MRI plays a major role to detect tumor foci and to rule in significant PCa. A low apparent diffusion coefficient (ADC) value indicates that high Gleason grade tumors are present. Conversely, the absence of any suspicious focus or foci with a high apparent diffusion coefficient value indicates either benign tissue or low-grade tumor Summary: mp-MRI Multiparametric MRI is a highly accurate filter to detect aggressive tumors and to avoid detection of insignificant cancer. There is growing evidence that it may be indicated in any man with an elevated Prostatic Specific Antigen level before considering whether an immediate biopsy should be performed or whether a simple follow-up should be the option.